2015
DOI: 10.5423/ppj.oa.10.2014.0113
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Inhibition of Cucumber Fusarium Wilt by Different Surfactinexcreting Strains of Bacillus subtilis

Abstract: Bacillus subtilis B006 strain effectively suppresses the cucumber fusarium wilt caused by Fusarium oxysporum f. sp. cucumerinum (Foc). The population dynamics of Foc, strain B006 and its surfactin over-producing mutant B841 and surfactin-deficient mutant B1020, in the rhizosphere were determined under greenhouse conditions to elucidate the importance of the lipopeptides excreted by these strains in suppressing Foc. Results showed that B. subtilis strain B006 effectively suppressed the disease in natural soil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Moreover, the quantity of surfactrin produced by different Bacillus strains is different. For example, Jia et al (2015) reported that C12-, C13- and C16-surfactin are more abundant than C14- and C15-surfactin in B. subtilis B841. While, B. subtilis BS-37 usually produces C15-surfactin as the major component ( Liu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the quantity of surfactrin produced by different Bacillus strains is different. For example, Jia et al (2015) reported that C12-, C13- and C16-surfactin are more abundant than C14- and C15-surfactin in B. subtilis B841. While, B. subtilis BS-37 usually produces C15-surfactin as the major component ( Liu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through successful colonization in rhizosphere and the production of antifungal metabolites, this strain performs good biocontrol efficacy in suppressing cucumber wilt disease caused by Fusarium oxysporum and pepper root rot caused by Phytophthora capsici . In addition, B. velezensis B6 could inhibit the multiplication and delay the spread of F. oxysporum in cucumber stems ( 2 , 3 ) to suppress the disease development. However, the genes related to the biocontrol functions of B. velezensis B6 are not well known.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Some reports indicate that Bacillus species can effectively promote plant growth and may be a candidate for a biological control agent (BCA) [16]. Jia et al [17] reported that the colonization of B. subtilis and suppression of F. oxysporum in the rhizosphere are important for Fusarium wilt disease control. Chen et al [18] investigated two sets of bacterial samples: Bacillus licheniformis (X-1) and Bacillus methylotrophicus (Z-1) both with a strong inhibitory effect on Fusarium wilt caused by F. oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%